Helicobacter pylori Western cagA genotype in Egyptian patients with upper gastrointestinal disease - Manal Diab; Mohamed Shemis; Doaa Gamal; Ahmed El-Shenawy; Maged El-Ghannam; Effat El-Sherbini; Mohamed Saber (Egyptian Journal of Medical Human Genetics, 2018)
Background: Infection with Helicobacter pylori (H. pylori) causes persistent gastritis that may progress to fatal gastric cancer. The cytotoxin-associated gene A protein (CagA), encoded by the cytotoxin-associated gene A (cagA) is the main virulence factor associated with more severe clinical outcomes. It is further divided into Western-type CagA and East Asian-type CagA. The East Asian-type CagA induces more cytoskeleton changes and is more likely to be associated with gastric cancer. Aim of the study: In the current study we aimed to identify the most prevalent H. pylori cagA genotype among Egyptian patients suffering from dyspepsia and to examine its possible correlation with the associated clinical condition. Patients and methods: Four biopsies were obtained from the antrum and angularis from each of 113 adult patients, who underwent upper endoscopy at the Endoscopy Unit, Theodor Bilharz Research Institute (TBRI) Hospital for the analysis of H. pylori by rapid urease test and detection of 16S rRNA. Nested PCR assay was used to determine cagA genotype. Results: Sixty (53.1%) dyspeptic patients were found infected with H. pylori. Although Egypt has a high prevalence of H. pylori infection, low prevalence of cagA was detected (26.5%). Western type cagA is the predominant type (62.5%) while East Asian type was not detected and others (37.5%) remain uncharacterized. Western-genotype cagA genotype was found in 80% of patients with peptic ulcer disease and 40% of patients with gastritis. Conclusion: Absence of the more virulent East Asian cagA genotype, which is the strongest risk factor for gastric carcinogenesis, may explain the very low gastric cancer rate among Egyptian population compared to other parts of the world. This finding demands further molecular studies using whole genome sequencing and more samples to determine the exact uncharacterized cagA genotype to identify the actual risk in developing gastroduodenal diseases in Egypt. Keywords: Helicobacter pylori, Endoscopic findings, Western type cagA, East-Asian cagA, Peptic ulcer, Gastritis